Is reappraisal always effective in modifying emotional reactions in females? The role of regulatory timing and goals. Issue 2 (11th January 2018) - Yan, Chunping; Lin, Na; Cui, Lixia; Zhang, Qin
Abstract: Introduction: Numerous studies have explored the effect of cognitive reappraisal before or after emotion‐inducing events. However, only a few studies have examined the influence of regulatory timing on the effectiveness of reappraisal. Thus, the aim of this study was to investigate the role of regulatory timing and goals in reappraisal regulation, which would help promote the specific application of cognitive reappraisal in emotion regulation. We hypothesized that decrease reappraisal would be more effective when initiated early rather than late, but increase reappraisal would be more effective when initiated in the emotional high‐activation phase. Methods: This study, via event‐related potential (ERP) technique, probed the influence of the timing and regulatory goal on negative emotion when reappraisal was introduced, respectively 500 ms before (anticipatory), 2, 000 ms after (online 2, 000 ms) picture onset (in Experiment 1), 500 ms after (online 500 ms) picture onset, and 1, 500 ms after (online 1, 500 ms) picture onset (in Experiment 2). Results: Based on the ERP results, under the anticipatory regulation condition, the LPP amplitude in the parietal area was significantly reduced by decrease reappraisal during 700–2, 100 ms after picture onset, and under the online 500 ms regulation condition, the LPP in central and parietal areas was significantly enhanced by increase reappraisal during 450–750 ms after regulatory cue onset. Moreover, our results showed that increase reappraisal evoked a larger prefrontal or frontal LPP than decrease reappraisal beginning at about 700 ms after picture onset under the anticipatory regulation condition and beginning at 450 ms after regulatory cue onset under the online 500 ms regulation condition, which may reflect increased cognitive effort and mental conflict associated with increase reappraisal. Conclusion: The anticipatory reappraisal successfully decreased negative emotion, and online 500 ms reappraisal successfully increased negative emotion. Our results support the hypothesis. Abstract : Regulatory timings have influence on effectiveness of cognitive reappraisal. Reappraisal successfully decreased negative emotion under the anticipatory regulation. Online 500 ms reappraisal successfully increased negative emotion. Increase reappraisal might need increased cognitive effort and more mental conflict.